Orientalist imagery in the films Il Bagno Turco, Zenne Dancer, and Auf der Anderen Seite - Dağlı, Sanem Peker (My University, 2019)
The power relations between the Orient and the West co-exist with a literary and scientific language on the Orient along with all the connotations and annotations which conjure up the idea of the Orient in popular imagination. Latent Orientalism refers to the unconscious and taken-for-granted conceptions on the Orient. It is this latency which naturalizes and legitimizes the given binarisms of Orientalism and renders it a hegemonic characteristic. Orientalism and its authority reside in the discourse it has become to spell the truth about the Orient. The works produced on the Orient can be analyzed in terms of the ways they replicate the same figures, images, styles or scenarios as reflections of the hegemony of Orientalism. The purpose of this study is to embark on a quest for Orientalist imagery in Turkey’s cinema on the trajectory of the films Il Bagno Turco aka Hamam by Ferzan Özpetek, Zenne Dancer aka Zenne by Caner Alper and Mehmet Binay, and Auf Der Anderen Seite aka Yaşamın Kıyısında by Fatih Akın. In this study, the systematic thoughts and ideas on the Orient and the concept of latent orientalism provide a basis in the analysis of the selected films from Turkey’s cinema. Depending on the premise that the dichotomies of colonial discourse and gender issues contribute to each other and cultivate together, the analyses in this study are also based on a search for Orientalist gaze in these films from a sexual difference perspective. The incentive in the film analyses is to search for various outbreaks of Orientalist discourse latent in the filmic texts to contribute to the discussions in the field.

Doğu ile Batı arasındaki iktidar ilişkileri, genel muhayyilede Doğu fikrini oluşturan tüm çağrışım ve yorumların yanı sıra, Doğu’ya dair yazınsal ve bilimsel bir dil ile birlikte var olur. Örtük Oryantalizm, Doğu’ya ilişkin bilinçaltı ve doğru kabul edilen düşüncelere karşılık gelir. Oryantalizmin benimsenmiş ikiliklerini doğal ve meşru hale getiren ve ona hegemonik bir karakter kazandıran işte tam da bu örtüklüktür. Oryantalizm ve sahip olduğu otorite, Doğu’ya ilişkin hakikati ortaya koymak üzere dönüştüğü söylemde saklıdır. Doğu’yu konu alan eserler, Oryantalizmin hegemonyasının yansımaları olarak aynı figürleri, imgeleri, stilleri ya da senaryoları tekraren kullanmaları bakımından ele alınıp incelenebilir. Bu çalışmanın amacı, Ferzan Özpetek’in Hamam (Il Bagno Turco), Caner Alper ve Mehmet Binay’ın Zenne (Zenne Dancer), ve Fatih Akın’ın Yaşamın Kıyısında (Auf Der Anderen Seite) filmleri yörüngesinde Türkiye Sineması’nda Oryantalist imgelemin izini sürmektir. Bu çalışmada incelenmek üzere seçilmiş olan filmlerin analizinde, Doğu üzerine üretilmiş olan sistematik düşünce ve fikirler ile örtük Oryantalizm kavramı baz alınmıştır. Kolonyal söylem ile toplumsal cinsiyet meselelerine ilişkin dikotomilerin birbirlerine katkıda bulundukları ve birlikte geliştikleri öncülüne dayanarak, bu çalışmadaki analizler aynı zamanda Oryantalist bakışın izini, cinsel fark perspektifinden de sürmektedir. Film analizlerindeki temel saik, alandaki tartışmalara katkıda bulunmak amacıyla, filmlerde örtük olan Oryantalist söylemin farklı tezahürlerine bakmaktır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Orientalism; Latent Orientalism; Colonial discourse; Sexual difference; Oryantalizm; Örtük oryantalizm; Kolonyal söylem; Cinsel fark